2015
DOI: 10.1371/journal.pone.0118217
|View full text |Cite|
|
Sign up to set email alerts
|

Addition of Lidocaine Injection Immediately before Physiotherapy for Frozen Shoulder: A Randomized Controlled Trial

Abstract: The intraarticular injection of lidocaine immediately before a physiotherapy session may relieve pain during the stretching and mobilization of the affected joint in patients with a frozen shoulder, thus enhancing the treatment effect. To compare the effects of intraarticular injection of lidocaine plus physiotherapy to that of physiotherapy alone in the treatment of a frozen shoulder, a prospective randomized controlled trial was conducted in the rehabilitation department of a private teaching hospital. Patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…Statistically significant differences were noted between two groups in terms of pain relief as reported earlier by Wei-Chun 20 Hsu et al . Similarly, the difference in ease of performing ADL between two groups was statistically significant, patients in Group A performing better.…”
Section: Original Article a Comparative Study Of Steroid Injection Wisupporting
confidence: 71%
See 1 more Smart Citation
“…Statistically significant differences were noted between two groups in terms of pain relief as reported earlier by Wei-Chun 20 Hsu et al . Similarly, the difference in ease of performing ADL between two groups was statistically significant, patients in Group A performing better.…”
Section: Original Article a Comparative Study Of Steroid Injection Wisupporting
confidence: 71%
“…The intra-articular injection of lignocaine immediately before a physiotherapy session may relieve pain during the stretching and mobilization of the affected joint in patients with a frozen shoulder, thus enhancing the treatment effect. As physical therapy (Physiotherapy) is the prime factor for its treatment, immediate pain relief is a major determinant for the patients to 20 follow it . The early the start of physical therapy, the sooner and better is the outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Strengthening of the rotator cuff muscles was performed by means of isometric and isotonic exercises with the use of a theraband and dumbbells and was combined with TENS and mobilization in the study by Rawat et al Moreover, the addition of supervised physiotherapy 359 including mobilization and stretching to a home exer-360 cise program had no significant effect in improving the 361 clinical outcomes compared to home exercises alone 362 in patients after the hydrodilatation procedure at one 363 year follow up [60]. Hsu et al [50] showed that the 364 introduction of 3 ml of 1% lidocaine injection prior 365 to physiotherapy was effective in relieving pain dur-366 ing stretching and mobilization and thereby improved 367 outcomes at six months follow up. Jellad et al [64] 368 introduced intra-articular distension (IAD) before and 369 after physiotherapy sessions to compare with the phys-370 iotherapy alone group for 12 weeks.…”
Section: Quality Reviewmentioning
confidence: 99%
“…Chen et al showed that text messages sent to patients by mobile phone to remind and encourage them significantly increased compliance with their own exercises and thus improved the mobility of the shoulder [22]. An intra-articular injection of lidocaine immediately before physiotherapy to improve patient compliance was also shown to be superior to pure physiotherapy in the treatment of shoulder stiffness [23]. However, the negative effects of local anaesthetics on cartilage should be taken into account when this procedure is performed [24].…”
Section: Physiotherapymentioning
confidence: 99%